Pengamalan Wanita Hamil dalam Masyarakat Melayu dari Perspektif Islam: The Practices of Pregnant Women in Malay Communities from An Islamic Perspective - Mohd Isa, Raihan; Man, Saadan; Abdul Rahman, Noor Naemah; Pauzi, Norhidayah (Jurnal Fiqh, 2019)
The rich and powerful Malays hold on to various tips and taboos inherited from previous generations covering all aspects of their lives. Among them are tips and taboos involving nutrition, beauty, safety and health aspects of pregnant women. This practice aims to preserve the health and safety of pregnant women from any disturbance related to the beliefs of the Malay community at that time. However, these tips and taboos need to be examined so that they do not contain elements that are contrary to Islamic values. This article discusses practices related to the tips and taboos for pregnant women among the Malay community according to an Islamic law perspective. The study uses library research (documentation method) by collecting data through primary and secondary sources and analyzed from an Islamic law perspective. The findings show that some tips and taboos that are in line with the teachings of Islam can be practiced, while some contradict with the values of Islam. In this regard, the community must be careful in practicing the traditions and beliefs so that they will not fall into the superstition trap.